Microbiological Analysis of Street Foods Sold in Kathmandu, Nepal (Tribhuvan University Journal of Microbiology, 2022)
Objectives: To investigate whether the street foods are potential source of pathogens or not.Methods: A total of 36 samples of different street foods were aseptically collected from different areas of Kathmandu Valley and was transported to laboratory. The bacterial load was enumerated using pour plate technique on plate count agar. Fungal load was enumerated using pour plate technique on potato dextrose agar and coliform load was also calculated using pour plate technique on VRBA. While Staphylococcus aureus was selectively detected on Mannitol Salt Agar. Escherichia coli was detected by observation of metallic sheen on Eosin Methylene Blue Agar.Results: The highest bacterial load was found on pani-puri with 70.4x103 cfu/ml and highest fungal load was found on samosa with 34.5x103 cfu/ml whereas the presence of coliforms was only detected in panipuri and chana chatpate. The food samples consisted of E. coli and S. aureus. E.coli was only detected from chana-chatpate. While the average Staphylococcal load was found to be highest in pani-puri (91.6x103 cfu/ml) and lowest in mo: mo (1.7x103 cfu/ml).Conclusion: This study concludes that E. coli and coliforms are the most common contaminant in channa chatpate sold in streets. Panipuri and channa chatpate sold in streets have the highest microbial loadand hence more chances of harboring potential pathogens. Street food sample in Kathmandu is mostly contaminated with the S. aureus.